2020
DOI: 10.1186/s12939-020-01304-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of objective income and perceived economic resources on self-rated health

Abstract: Background Several studies have demonstrated that self-rated health status is affected by socioeconomic variables. However, there is little knowledge about whether perceived economic resources affect people’s health. The purpose of this study is to examine the relationship between self-rated health status and different measures of income. Specifically, the effect of both objective income and perceived economic resources are estimated for a very large sample of households in Italy. By estimating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 46 publications
3
25
0
4
Order By: Relevance
“…The results of the present study also show that subjective income status measured by self-perceived income sufficiency had a significant association in cognitive functioning in older ages. It is noteworthy that the measure of subjective income status has been used in past studies to assess the economic well-being as well as satisfaction and stress levels [ 42 , 43 ], and is recommended to assess the resource availability among underserved populations [ 14 ]. In a study using data from World Health Organization’s Study on global AGEing and adult health (SAGE), perceived income adequacy was found to be significantly associated with self-rated health among older adults [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study also show that subjective income status measured by self-perceived income sufficiency had a significant association in cognitive functioning in older ages. It is noteworthy that the measure of subjective income status has been used in past studies to assess the economic well-being as well as satisfaction and stress levels [ 42 , 43 ], and is recommended to assess the resource availability among underserved populations [ 14 ]. In a study using data from World Health Organization’s Study on global AGEing and adult health (SAGE), perceived income adequacy was found to be significantly associated with self-rated health among older adults [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Não obstante não tenha sido verificada associação significativa entre esta variável e autopercepção de saúde no presente estudo, existem evidências de forte associação entre elas na literatura (Kraja, Kraja, Cakerri, & Burazeri, 2016). A escolaridade é um indicador estreitamente relacionado a emprego, renda, posse de bens e acesso a serviços, aspectos socioeconômicos capazes de prejudicar a saúde percebida (Cialani & Mortazavi, 2020). De acordo com os autores, o ensino superior ajuda as pessoas a melhorarem suas habilidades para o alcance dos objetivos de vida e ter um estilo de vida saudável.…”
Section: Discussionunclassified
“…A predominância de mulheres com renda familiar menor ou igual a três salários-mínimos confirma o perfil da população constituída da maioria de pessoas com baixo poder aquisitivo. Mesmo não tendo associação estatística entre essa variável e autopercepção de saúde, considera-se que o impacto psicossocial de pertencer a uma classe social específica influencia a saúde física dos indivíduos e a forma como percebem a sua saúde, pois reflete a capacidade dos indivíduos de atender às suas necessidades e a falta de recursos econômicos relaciona-se a maior probabilidade de ter uma percepção de saúde insatisfatória (Cialani & Mortazavi, 2020). Ser membro de uma família com privação material aumenta as chances de perceber a saúde de forma negativa (López Del Amo González, Benítez & Martín-Martín, 2018).…”
Section: Discussionunclassified
“…The literature shows that demographic, economic and factors related to the presence of chronic noncommunicable diseases influence the way people can assess their own health status ( Szwarcwald et al, 2015 ; Cialani & Mortazavi, 2020 ; Haj-Younes et al, 2020 ). In this sense, in order to characterize the sample and adjust the multivariate analyses of the present research, the following variables were collected through questionnaire: sex (male/female); age in years (18–29 years; 30–39 years; 40–49 years; 50–59 years; 60–69 years; ≥ 70 years); schooling in years of study (≥ 12 years; 9–11 years; ≤ 8 years); skin color (white; brown; black; yellow; indigenous); marital status (single; married or stable relationship; divorced or widowed).…”
Section: Methodsmentioning
confidence: 99%